(untitled) (REVISTA NODO, 2013)
The article deals with the issue of architectural education and professionalization in Latin America. Beginning with a succinct depiction provided by United Nations, among others, in which the subcontinent comes out as the most urbanized region of the world, and a place where social and economic inequalities uphold over 124 million people living in poverty —more than 25% of all city dwellers—, afar from comprising 5 out of the 20 worst ranked nations in regards to absolute environmental impact, the authors raise the question of how to build a more suitable urban milieu for Latin America’s future out from the academia. In this context, the school of architecture at the Antonio Nariño University (UAN, as per the Spanish acronym), benefiting from its presence in 9 Colombian cities Bogota, Neiva, Palmira, Ibague, Villavicencio, Bucaramanga, Cucuta, Popayan y Puerto Colombia—, aims to bring up its students under an actual state of urban, regional and spatial conditions, revolving its undergraduate program around a curricular structure composed of lines of study, thematic units, key concepts’ application and research projects.